Digitizing Monetary Ecologies: Intended and Unintended Consequences of Introducing a Financial Management App in a Low-Resource Setting - Hulikal Muralidhar, Srihari; Bossen, Claus; Mehra, Apurv; O'Neill, Jacki (Proceedings of ACM on Human-Computer Interaction, 2018)
This paper reports on the changes in the monetary ecology around loan payments shortly after the introduction of a mobile app in Karnataka, India. The app was designed to be used by a social enterprise working with auto-rickshaw drivers by enabling them to take out loans to buy their auto-rickshaws. The app was intended to provide timely loan information for the drivers and support the collaborative work of loan collection and payment. We report on the initial experiences with the app, exploring both its intended and its unintended consequences. We do this by comparing the workflows before and after introduction of the app through the lens of the three phases of moneywork: that is, what changed during pre-, at-, and post-transaction moments. Whilst the app certainly streamlined the workflows, unintended consequences arose from making previously hidden work visible, as well the shifting of control towards the back office, reducing field agents’ flexibility.
Article No. 72